Can "sense of presence" experiences in bereavement be conceptualised as spiritual phenomena? - Steffen, Edith (Mental health, religion & culture, 2010)
This article explores the possibility of conceptualising the frequently occurring experience of "sensing the presence of the deceased" in bereavement as a spiritual phenomenon and examines how such a conceptualisation can be related to two recent perspectives in the field of bereavement research, "continuing bonds" and "meaning-making." It is argued that "sense of presence" experiences are expressions of the continuing relationship with the deceased that can be spiritually understood but that pose various challenges for their meaningful integration into the bereaved person's worldview or meaning structures-something that may need to be more explicitly incorporated into current theoretical frameworks. It is suggested that these experiences can be the catalyst for "post-traumatic growth" through a socially mediated and interactive narrative exploration and that this has important implications for bereavement counselling and therapy.